2018
DOI: 10.25077/mka.v41.i2.p59-68.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan pasien diabetes melitus tipe 2 dan hubungannya dengan kepatuhan minum obat di Puskesmas Mandau Kabupaten Bengkalis

Abstract: Diabetes melitus merupakan penyakit yang memerlukan terapi jangka panjang dan dapat menimbulkan komplikasi di berbagai organ. Pengetahuan merupakan faktor penting untuk terbentuknya perilaku kesehatan yang baik termasuk dalam kepatuhan minum obat. Tujuan: Mendapatkan gambaran tentang korelasi  antara pengetahuan dan  kepatuhan minum obat pasien DM tipe 2 di Puskesmas Mandau Kabupaten Bengkalis. Metode: Studi observasional dengan desain crosssectional  dilakukan pada pasien diabetes melitus (DM) Tipe 2 di Puske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 2 publications
0
6
0
24
Order By: Relevance
“…Pengetahuan tentang penyakit DM merupakan sarana yang dapat membantu pasien dalam melakukan penanganan terhadap DM (Nazriati, Pratiwi, & Restuastuti, 2018). Pengetahuan tersebut dapat diperoleh salah satunya melalui tenaga kesehatan yaitu perawat.…”
Section: Peran Perawat Sebagai Edukatorunclassified
“…Pengetahuan tentang penyakit DM merupakan sarana yang dapat membantu pasien dalam melakukan penanganan terhadap DM (Nazriati, Pratiwi, & Restuastuti, 2018). Pengetahuan tersebut dapat diperoleh salah satunya melalui tenaga kesehatan yaitu perawat.…”
Section: Peran Perawat Sebagai Edukatorunclassified
“…Adherence in patients with type 2 diabetes is generally defined as the level of behavior of someone who is getting treatment for diet, taking medication and carrying out a lifestyle in accordance with the recommendations of health care providers [24] Patients who do not understand DM, often do not comply with DM treatment [25] The success of DM treatment is highly dependent on the patient's compliance with taking medication. Several previous studies on the relationship between knowledge and adherence to taking medication have shown different results [26][27][28] .…”
Section: Discussionmentioning
confidence: 89%
“…If the dose is overused or if the drug is consumed more frequently than the recommended recommendation, it can create greater side effects. Problems like this often arise in patients who forget to take one dose of the drug and double the next dose [29] The level of knowledge is one of the factors in influencing the level of adherence to take medication, so providing indepth information about diabetes mellitus is very important to do so that the level of adherence to take medication increases and the risk of disease severity and complications decreases, and blood glucose can be controlled [26] Knowledge is a very important domain for action to be formed, the necessary elements include understanding what is done, beliefs about the benefits and truth of what is done and the means needed to do it. Action is an internal response after thought and knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of education helps individuals get more and more information because the more information obtained, the better their level of knowledge (Nazriati, Pratiwi, & Restuastuti, 2018). A good level of knowledge can increase the compliance of patients with pulmonary TB to take medication regularly so that they can prevent transmission to others and improve planned treatment behavior.…”
Section: Effect Of Problem Management On Pulmonary Tb Treatment Behaviormentioning
confidence: 99%